PENDIDIKAN DALAM PERSPEKTIF TEORI SOSIOLOGI - Rasyid, Muhammad Rusydi (AULADUNA: Jurnal Pendidikan Dasar Islam, 2015)
Abstract: Sociology is an educational study approach, delivering to understand the relation of sociology to education. Sociology of education have diverse perspectives, in line with the diversity of perspectives that occurred in the study of sociology in general. Also understand the distribution of educational sociology perspective oriented in macro and micro with a number of theories within its perspective. Sociology of education can help to understand the planning, the implementation process and the implications of the implementation of certain programs or policies. In the division of educational sociology perspectives, it will be demonstrated the differences in educational sociology oriented in macro and micro studies. Beside that, it also presents the structural functional theory, the conflict theory, and the theory of symbolic interactionism. Sociology contributes significantly for those interested in efforts to conduct a critical assessment of what is happening in society. If we can understand what is in the society, then great opportunities for us to be able to control the changes in society.Abstrak: Sosiologi merupakan pendekatan studi tentang pendidikan, menghantar-kan untuk memahami kaitannya sosiologi dengan pendidikan. Sosiologi pendidikan memiliki perspektif yang beragam, sejalan dengan keragaman yang terjadi dalam perspektif kajian sosiologi pada umumnya. Juga memahami pembagian perspektif sosiologi pendidikan yang berorientasi makro dan mikro dengan sejumlah teori yang berpayung di dalam perspektifnya. Sosiologi pendidikan dapat membantu memahami peren-canaan, proses implementasi dan implikasi penerapan progam maupun kebijakan tertentu. Dalam pembagian perspektif sosiologi pendidikan akan diperlihatkan perbedaan sosiologi pendidikan yang berorientasi pada dimensi kajian makro dan dimensi kajian mikro. Selain itu, dipaparkan pula Teori Fungsional Struktural, Teori Konflik, Teori interak-sionisme simbolik. Sosiologi memberi sumbangan yang berarti bagi mereka yang tertarik dalam upaya melakukan kajian kritis terhadap apa yang terjadi di masyarakat. Jika kita bisa memahami apa yang ada di lingkungan sekitar, maka besar peluang kita untuk dapat mengendalikan perubahan masyarakat.